Improvement of Village Economy Through The Role of The Home Industry - Hersa Farida Qoriani; Indra Hidayatullah (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
This rice cracker business can actually improve the economy of rice crackers residents of Sidokerto Village, Buduran , Sidoarjo. Even this business opens up jobs for the residents of Sidokerto, especially mothers. This research is a qualitative descriptive study, which is to present a complete picture of a phenomenon for exploration or clarification. The results of data or research results are as they are, without any manipulation or other treatment processes. The results of the research carried out concluded that: 1) The role of the small puli cracker industry in improving the economy of Sidokerto, Buduran, Sidoarjo is to provide and increase work motivation, work resilience by providing training and skills to the surrounding community. The existence of a small puli cracker industry is very important and can help people with job opportunities to become laborers in helping to make puli crackers. With this industry, people's income will increase and it can improve the village economy. The small puli cracker industry has a good influence on the economic growth of the local community. 2) The inhibiting factors for the small puli cracker industry include: limited capital, limited technical ability, limited marketing ability.